Prediction of hope, physical health, and mental health by mediating variable of religious spiritual well-being in elderly. Issue 10 (25th November 2020) - Abdolahrezaee, Neda; Khanmohammadi, Arsalan; Dadfar, Mahboubeh; Rashedi, Vahid; Behnam, Liela
ABSTRACT: The Religious Spiritual Well-being (RSWB) is a new concept relevant to healthcare systems. Hope has an important role in coping with psychosocial problems in aging. Physical problems are common in aging and threaten mental health in this age group. The aim of this study was to investigate the relationship between RSWB with hope, physical health, and mental health in the elderly. The scales included the Multidimensional Inventory for Religious Spiritual Well-Being (MI RSWB 48), Adult Hope Scale (AHS), Patient Health Questionnaire-15 (PHQ-15), and General Health Questionnaire-28 (GHQ-28) and were administered to 100 elderly people. Hope Immanent (HI) and Experiences of Sense and Meaning (SM) subscales and MI RSWB 48 total scores were positively correlated with hope and mental health; HI subscale and MI RSWB 48 total scores were negative correlated with physical health. The RSWB dimensions predicted hope (36%), physical health (32%), and mental health (53%), respectively. Psycho-educational programs would be useful to increase RSWB in order to enhance hope, physical health, and mental health in the elderly.